Influence of microbially fermented 2´-fucosyllactose on neuronal-like cell activity in an in vitro co-culture system - Kuntz, Sabine; Kunz, Clemens; Borsch, Christian; Hill, David; Morrin, Sinéad; Buck, Rachael; Rudloff, Silvia (Frontiers in Nutrition, 2024)
Scope: 2´-fucosyllactose (2´-FL) is the most abundant oligosaccharide in human milk and it has been associated with a number of biological functions including improved learning. It is not clear, however, whether 2´-FL or a cleavage product could influence neuronal cell activity. Thus, we investigated the effects of 2´-FL, its monosaccharide fucose (Fuc) and microbial fermented 2´-FL and Fuc on parameters of neuronal cell activity in an intestinal-neuronal transwell co-culture system in vitro. Methods: Native 13 C-labeled 2´-FL and 13 C-Fuc or their metabolites after fermentation by Bifidobacterium (B.) longum ssp. infantis and B. breve, taken from the lag-, log-and stationary (stat-) growth phases of batch cultures were applied to the apical compartment of the co-culture system with Caco-2 cells representing the intestinal layer and all-trans retinoic acid-differentiated SH-SY5Y (SH-SY5YATRA) cells mimicking neuronal-like cells. After 3h of incubation, the culture medium in the basal compartment was monitored for 13 C-enrichment by using Elemental Analysis Isotope-Ratio Mass Spectrometry (EA-IRMS) and effects on cell viability, plasma and mitochondrial membrane potential as well as neurotransmitter activation (BDNF, GABA, choline and glutamate) of SH-SY5YATRA cells were determined. Furthermore, these effects were also measured by direct application of 13 C-2´-FL und 13 C-Fuc to SH-SY5YATRA cells. Results: While no effects on neuronal-like cell activities were observed after incubation of SH-SY5YATRA cells with intact 2´-FL or Fuc, supernatants from the statgrowth phase of 2´-FL, fermented by B. longum ssp. infantis alone and together with B. breve, significantly induced BDNF release from SH-SY5YATRA cells. No such effects were found with 2´-FL, Fuc or their fermentation products from B. breve. This BDNF releasing effect was a result of an enhanced vesicular release, which was confirmed by the use of the Ca 2+ -channel blocker verapamil. Concomitant with this, 13 C-enrichment was also observed in the basal compartment when supernatants from the stat-growth phase of fermentation by B. longum ssp. infantis alone or together with B. breve were used. Conclusions: These results suggest that microbial products of 2´-FL rather than the oligosaccharide itself may influence neuronal cell activities.